A review of fossil taxa of Microphorinae (Diptera, Dolichopodidae sensu lato), with redescription of the Eocene genus Meghyperiella Meunier - Shamshev, Igor V.; Perkovsky, Evgeny E. (Zootaxa, 2022)
The current data on fossil empidoid flies of the subfamily Microphorinae (Dolichopodidae sensu lato) are summarized. The extinct taxa of this group includes five genera (Avenaphora Grimaldi & Cumming, Curvus Kaddumi, Meghyperiella Meunier, Microphorites Hennig, Pristinmicrophor Tang, Shi, Wang & Yang) and 17 described species (one species in extant genus Microphor Macquart and two species in Schistostoma Becker). One more possible fossil microphorine genus Microcathophorites is treated as a nomen nudum. Microphorines were found from different deposits dated over a very broad geological temporal range from Lower Cretaceous to the Eocene. However, the majority of them are currently known from the Cretaceous (five genera and 13 (14?) species). Only two genera and four (three?) species were found from the Eocene. More precise definitions of Curvus, Meghyperiella, Microphorites and Pristinmicrophor as well as their possible relationships are discussed. In addition, the little known Eocene genus Meghyperiella is redescribed and newly recorded from Rovno amber (Ukraine). An identification key to all fossil taxa of microphorines is compiled for the first time.